Regulation and macroeconomic performance - Loayza, Norman, 1964- 1964- (Policy research working paper, 2005)
"Regulation is purportedly enacted to serve specific social purposes. In reality, however, it follows a more complex political economy process, where legitimate social goals are mixed with the objectives of particular interest groups. Whatever its justification and objectives, regulation can have potentially significant macroeconomic consequences by helping or hampering the dynamics of economic restructuring and resource reallocation that underlie the growth process. Loayza, Oviedo, and Serven provide an empirical analysis of the macroeconomic impact of regulation. They first characterize the stylized facts on regulation across the world using a set of newly constructed, comprehensive indicators of regulation in a large number of countries in the 1990s. Using these indicators, the authors study the effects of regulation on economic growth and macroeconomic volatility using cross-country regression analysis. In particular, they consider whether the effects of regulation are affected by the country's level of institutional development. Finally, their analysis controls for the likely endogeneity of regulation with respect to macroeconomic performance. The authors conclude that a heavier regulatory burden reduces growth and increases volatility, although these effects are smaller the higher the quality of the overall institutional framework. This paper--a product of the Growth and Investment Team, Development Research Group--is part of a larger effort in the group to understand the process of economic reform"--World Bank web site